2022
DOI: 10.1111/socf.12836
|View full text |Cite
|
Sign up to set email alerts
|

Nationalism and the Politics of Nostalgia1

Abstract: This article contributes to the analysis of the politics of nostalgia by focusing on its content, conditions, and mechanisms. Frame theory is used to understand the contested nature of nostalgia through the central framing of the past. We explore ways in which nostalgia relates to ethnic nationalism and populism and its close relationship to the rhetoric of the populist radical right. Components of nostalgia that stand out as particularly significant is the history of decline and loss. Whereas nostalgia is uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Radical right voting is associated with higher magnitudes of group‐based but not personal nostalgia. While this finding speaks to the relevance of radical right rhetoric shaping people's experiences (e.g., Elgenius & Rydgren, 2022; Mols & Jetten, 2020), it also shows that the above‐presented coefficients need to be interpreted cautiously. Group‐based nostalgia is associated with radical right voting intentions, sympathy for the party and its leader and more culturally conservative attitudes when accounting for temporal shocks and a series of background variables.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Radical right voting is associated with higher magnitudes of group‐based but not personal nostalgia. While this finding speaks to the relevance of radical right rhetoric shaping people's experiences (e.g., Elgenius & Rydgren, 2022; Mols & Jetten, 2020), it also shows that the above‐presented coefficients need to be interpreted cautiously. Group‐based nostalgia is associated with radical right voting intentions, sympathy for the party and its leader and more culturally conservative attitudes when accounting for temporal shocks and a series of background variables.…”
Section: Resultsmentioning
confidence: 80%
“…Why is nostalgia, and particularly its group‐based contents, associated with radical right support? Arguably, preferences for a more ethnically homogenous past will explain parts of it, such that people support exclusionary parties if they feel that societies have diversified too much (e.g., Elgenius & Rydgren, 2022; Smeekes et al., 2021). But, as shown in previous research (Hepper et al., 2014; Wildschut et al., 2006), nostalgia is a widely and frequently experienced emotion, and the present paper confirmed that its experience is not limited to radical right voters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations